Degree of conversion of two lingual retainer adhesives cured with different light sources - (:unkn) unknown (OXFORD UNIV PRESS, 2005)
The aim of this study was to evaluate the degree of conversion (DC) of two lingual retainer adhesives, Transbond Lingual Retainer (TLR) and Light Cure Retainer (LCR), cured with a fast halogen light, a plasma arc light and a light-emitting diode (LED) at various curing times. A conventional halogen light served as the control. One hundred adhesive samples (five per group) were cured for 5, 10 or 15 seconds with an Optilux 501 (fast halogen light), for 3, 6 or 9 seconds with a Power Pac (plasma arc light), or for 10, 20 or 40 seconds with an Elipar Freelight (LED). Samples cured for 40 seconds with the conventional halogen lamp were used as the controls. Absorbance peaks were recorded using Fourier transform infrared (FT-IR) spectroscopy. DC values were calculated. Data were analysed using Kruskal-Wallis and Mann-Whitney U-tests. For the TLR, the highest DC values were achieved in 6 and 9 seconds with the plasma arc light. Curing with the fast halogen light for 15 seconds and with the LED for 40 seconds produced statistically similar DC values, but these were lower than those with the plasma arc light. All of these light exposures yielded a statistically significantly higher DC than 40 seconds of conventional halogen light curing. The highest DC value for the LCR was achieved in 15 seconds with the fast halogen light, then the plasma arc light curing for 6 seconds. These two combinations produced a statistically significantly higher DC when compared with the 40 seconds of conventional halogen light curing. The lowest DC for the LCR was achieved with 10 seconds of LED curing. The overall DC of the LCR was significantly higher than that of the TLR. The results suggest that a similar or higher DC than the control values could be achieved in 6-9 seconds by plasma arc curing, in 10-15 seconds by fast halogen curing or in 20 seconds by LED curing.
Keywords: ORTHODONTIC ADHESIVES; DENTAL COMPOSITE; RESTORATIVE MATERIALS; CURING UNITS; BIS-GMA; RESIN; POLYMERIZATION; HALOGEN; PLASMA; DIODES